Influence study of flue gas on chromium acetate/HPAM gel in flue gas flooding reservoir. (1st February 2023) - Qiao, Wenli; Zhang, Guicai; Ge, Jijiang; Li, Jianda; Jiang, Ping; Pei, Haihua
Abstract: Polymer gels are potential plugging agents for gas mobility control in flue gas flooding reservoirs. However, the influence of flue gas on performances of polymer gels have not been clearly clarified so far. In this study, the effect mechanism of flue gas on chromium acetate/partially hydrolyzed polyacrylamide (HPAM) gel system has been elucidated in detail. Dynamic light scattering (DLS) and polymer rheological tests demonstrated that CO2 composed in flue gas altered the HPAM configuration by the decrease of hydrodynamic radius (Rh ) and polymer viscosity. Moreover, CO2 delayed the chromium acetate cyclic trimer dissociating into linear trimer and retarded the cross-linking process, which weakened the gelation performance and gel strength. The O2 composed in flue gas led to polymer degradation and seriously impaired the gel long-term stability. Fourier transform infrared spectroscopy (FTIR) analysis revealed that the breakage of Cr-O bond and the disruption of gel network structure were induced by the comprehensive effect of O2 and CO2 .